Effect of Repeated Weld Repairs on Microstructure and Mechanical Properties of Heat-Affected Zone in CA6NM Stainless Steel - Peng Liu; Jien Ma; Youtong Fang; Bowen Xu; Lin Qiu (Advances in Materials Science and Engineering)
The low-carbon martensitic stainless steel CA6NM is widely used in the impellers of hydroelectric and nuclear power units due to its advantages of high hardness, corrosion fatigue strength, and good fracture toughness. In order to analyze the number of repair welding times on the properties of heat-affected zone (HAZ, the most unstable area of welded joint property) in CA6NM, the microstructure and mechanical properties of HAZ with once-repaired welds (1R) and twice-repaired welds (2R) were tested. Through data analysis, the following conclusions are drawn for welded joints: (1) the grain size of HAZ with a different number of repair welding processes is smaller than that of the base material; (2) the density of texture concentration is reduced and the directionality is not obvious; (3) the density of twins and dislocations are increased; (4) the hardness and impact energy of HAZ of the 1R and 2R specimens are higher than that of the base material.